2022
DOI: 10.1186/s12889-022-14434-9
|View full text |Cite
|
Sign up to set email alerts
|

Wealth disparity and frailty among community-dwelling older adults in India

Abstract: Background Due to the vast socioeconomic diversity among its residents, studying health inequality in India is of particular interest. This study aimed to investigate the wealth-based inequalities in physical frailty and to quantify the contributions of potential predictors of frailty to this inequality. Methods Data were drawn from the first wave of the Longitudinal Ageing Study in India (LASI) conducted during 2017–18. Logistic regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Research has recently been carried out on trends associated with health inequalities, although most have been conducted in high-income countries in the northern hemisphere ( Katikireddi et al, 2020 ; Saravanakumar et al, 2022 ; Tsimbos, 2010 ). It has been consistently observed that wealth is strongly associated with mortality throughout adult life ( Katikireddi et al, 2020 ; Makaroun et al, 2017 ), although some studies suggest that this association tends to attenuate in old age ( Huisman, 2004 ; Reques et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has recently been carried out on trends associated with health inequalities, although most have been conducted in high-income countries in the northern hemisphere ( Katikireddi et al, 2020 ; Saravanakumar et al, 2022 ; Tsimbos, 2010 ). It has been consistently observed that wealth is strongly associated with mortality throughout adult life ( Katikireddi et al, 2020 ; Makaroun et al, 2017 ), although some studies suggest that this association tends to attenuate in old age ( Huisman, 2004 ; Reques et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent study examined the magnitude of oral health inequalities among older people using longitudinal data from Japan and Singapore, reporting that oral health inequalities increased over time in both countries, but mainly in Singapore ( Kiuchi et al, 2023 ). Nevertheless, studies on health inequalities with older adults have been primarily cross-sectional, and the results have shown that frailty, depression, functional limitations, chronic conditions, falls, low muscle mass, and cognitive impairment are concentrated in older people with a disadvantaged socioeconomic level ( Azizabadi et al, 2022 ; Katikireddi et al, 2020 ; Makaroun et al, 2017 ; Salinas-Rodríguez et al, 2019 ; Saravanakumar et al, 2022 ; Shang & Wei, 2023 ; Sharma & Pradhan, 2023 ; Tsimbos, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is associated with escalated health care costs, 4 driven by an inflated risk for acute illness, falls, injuries, disability, hospitalisation, institutionalisation, and mortality 5 . As such, physical frailty is a serious public health issue worldwide and particularly so in India given that the prevalence of frailty among Indians is significantly higher relative to their counterparts in other low and middle‐income countries (LMICs) 6–9 . Nonetheless, we are yet to ascertain the relevance of physical frailty for life satisfaction among older Indians and whether this association varies for men and women.…”
Section: Introductionmentioning
confidence: 99%